Deconstructing george w. bush: some observations (2005)
The following essay seeks to distinguish some relevant factors which permitted a G. W. Bush presidency. Among the composite pieces of the puzzle: G. W. the man, the political dynamics which surround him, and the powerful machine that helped him into office. No less relevant, is the political culture that dominates his administration and permeates his electorate, especially the rising influence of the South, and its implications. Finally, the wider context of the collective unconscious must be addressed. This deeper angle best puts into perspective the recent success of G. W. Bush and the ideology he represents. A section entitled “Fear” ties the individuals, and the machine, to a long-term, and largely instinctual impulse of nationalism to resist the penetration and encroachment of a hostile outside world. Because the anxiety of being infiltrated calls attention to those margins underscored by Derrida, we thought it appropriate to entitle this contribution Deconstructing George W. Bush.